Protective effects of atorvastatin and quercetin on isoprenaline-induced myocardial infarction in rats - Mai A. Zaafan; Hala F. Zaki; Amany I. El-Brairy; Sanaa A. Kenawy (Faculty of Pharmacy, Cairo University, 2013)
Myocardial infarction (MI) continues to be a major public health problem in the world. Statins exhibit cardio-protective effects by several mechanisms beyond their lipid lowering activity. Quercetin is a natural flavonoid that possesses significant anti-oxidant and antiinflammatory activities. The present study aimed to investigate the effects of pretreatment with atorvastatin (10 mg/kg) and quercetin (50 mg/kg), as well as their combination on isoprenaline-induced MI in rats. Markers chosen to assess cardiac damage included serum activity of creatine kinase-MB (CK-MB) and serum level of cardiac troponin-I (cTn-I), as well as oxidative stress and inflammatory biomarkers including serum levels of C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α), and interleukin-10 (IL-10) as well as cardiac contents of lipid peroxides, reduced glutathione (GSH), and nitrite. Furthermore, ECG monitoring and histological examinations of cardiac tissues were done. Isoprenaline increased serum CK-MB activity and cTn-I level as well as inflammatory and oxidative stress biomarkers. In addition, it produced ST-segment elevation and degenerative changes in heart tissues. Pretreatment with atorvastatin suppressed significantly the elevated levels of cTn-I, CRP, TNF-α, and IL-10 in serum coupled with reduction in cardiac lipid peroxides; however, it increased cardiac nitrite content. Quercetin decreased isoprenaline-induced changes in oxidative stress and inflammatory biomarkers with marked improvement in ECG and histopathologic alterations. Combination of quercetin with atorvastatin resulted in similar protective effects. In conclusion, quercetin can be regarded as a promising cardio-protective natural agent in MI alone or combined with atorvastatin.